Mothers' perspective about factors that influence preterm newborn breastfeeding: scoping review - Maria José Nogueira; Sandra Ribeiro; Carmen Silva; Paula Pereira; Delfina Teixeira (Instituto Politécnico de Viseu, 2024)
Introduction: Premature infant breastfeeding depends on the maternal perspective, which is influenced by positive and negative factors. Objective: To map factors that influence the breastfeeding of PN from the maternal perspective. Methods: Scoping Review following the Joanna Briggs Institute (JBI) and PRISMA ScR methodology. Data search for articles was carried out on Web of Science, Core Collection via Web of Science, b-On with full text, and PubMed between December 2019 and January 2021, available in full text in Spanish, Portuguese, and English. Of the 5.769 articles identified, scrutinized by title, abstract, and inclusion and exclusion criteria, the sample comprises 10 articles that meet the inclusion criteria. Results: Mothers' most reported difficulties are fears, stress, anxiety, insecurity, prematurity, Neonatal Intensive Care Unit environment, baby separation, breastfeeding, and milk extraction difficulties. As facilitators, mothers point out the nurse´s role in building the mother-child bonds. Conclusion: The paper informs about positive and negative factors in breastfeeding premature infants from the maternal point of view. Mothers need active support and professional guidance to promote and engage in good breastfeeding practices. From the maternal perspective, nurses are active players in promoting, protecting, and educating families about breastfeeding, mother-centered care, and mother-child bonding.